Utility of the Assessment Measures of the Financial Condition in Hospitality on a Sample of Selected Voivodships - Mokrzycka, Katarzyna (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The business activity of medical units is assessed on the basis of economic resources that could allow to assess the effectiveness of the examined business entity. The set of analytical measures and indicators is helpful in assessing the financial condition of the medical institution. The article aims to assess the utility of measures of the financial position of medical units in three selected voivodships: podkarpackie, małopolskie and lubelskie in 2014-2016. In order to achieve the goal, sources necessary for the analysis of the institutions’ indicators were used. The work contains an overview of popular Polish models of discriminant analysis in the field of forecasting the bankruptcy of medical units. Changes in the business environment affect the current financial condition and the ability to continue operations. The accuracy of bankruptcy forecasts depends to a large extent on the rapidly changing external environment. The conclusion from the above considerations may be the statement that in the process of forecasting bankruptcy, one can not rely only on financial indicators from the past, and they can be modified with time variables indicating the condition of the economic situation.